Vehicular Ramming Attacks: Assessing the Effectiveness of Situational Crime Prevention Using Crime Script Analysis - Williams, Alex (Terrorism and political violence, 2022)
The theoretical basis of Situational Crime Prevention (SCP) posits that to reduce crime it is first necessary to understand the interaction between the physical environment and criminal decision making. Situational efforts are commonly applied to specific crimes that are frequent in nature and, due to regular interaction with situational determinants, occur within temporal and spatial clusters. However, SCP is also regularly employed to prevent less frequent crimes, such as terrorist events. The application of SCP has potential to be highly effective for the now common occurrence of ideologically-motivated vehicle ramming attacks (VRAs). However, as SCP measures must be targeted and specific to crime events, it is necessary to first identify common features of the events under scrutiny. One analytical method used to inform the application of SCP through identification of common features of VRAs is crime scripting. This paper develops a crime script of twenty VRAs between 2008 and 2019. The results are analyzed to evaluate the effectiveness of existing SCP initiatives, and identify further opportunities to implement SCP to prevent and mitigate against the impact of VRAs.